(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
Organisations these days are growing rapidly, and both operational activities and business networks tend to use business unit strategies to overcome operational complexity. This constantly growing environment can significantly impact multinational transfer pricing practices. The research aims to look at the historical evolution and understand how the transfer pricing concept was changed over time and how the accounting legislation influenced the concept. One tool to achieve this goal is historiography and documentary research, which we applied to make it an accessible topic for further applications, studies, and analysis.